The research on enhancing the strength and durability of pipeline connection ports using arc welding additive manufacturing - Xiaoben Chen; Bo Zhang; Fanglin Shen; Chunxiao Jiao; Jingshu Chang; Chuan Feng; Wei Li (PLoS ONE, 2025)
In long-distance pipelines, the connection between pipelines is often the weakest link. During the manufacturing process of pipelines, roundness errors or defects are inevitable, and the greater the difference between the maximum and minimum diameters, the greater the impact on the strength of pipeline connections. At present, the main method to improve the pipe end is casting upsetting. However, there are currently no reports on using additive manufacturing technology to optimize pipeline ellipticity and improve pipe end strength and stiffness. This article solves the problem of weak weld strength at the connection end of oil pipelines and proposes for the first time the method of using arc additive manufacturing technology to thicken and reinforce the pipe end. By analyzing the ellipticity of the pipe end, arc based additive manufacturing technology is used to thicken the pipe end, thereby improving the strength and stiffness of the pipeline connection weld. This paper establishes a mathematical model for optimizing the design of pipeline connection ends, with remanufacturing thickness, length, and pipe end radius as design variables and pipe end strength and stiffness as constraints, and obtains the optimal parameter combination. The optimization results show that under typical working conditions, the optimized pipe end strength is significantly improved, the strain is significantly reduced, and the pipeline can withstand higher pressure, thereby improving the overall reliability and safety of the pipeline.